Long pulse thermography investigations of basalt fiber reinforced composite. (December 2018) - Kalyanavalli, V.; Ramadhas, T.K. Abilasha; Sastikumar, D.
Abstract: The long pulse thermography is a suitable technique for detection and quantification of defects in low thermal conducting materials, especially for composites. Basalt fiber reinforced epoxy composite is studied for determining defect depths using long pulse thermography. Flat bottom holes with specified depths and sizes are made in the composite for simulating delamination defects. Thermal images of the specimen are studied to obtain thermal contrast and characteristic peak time. A relation between the slope peak time and defect depth by peak derivative method is obtained analytically for long-pulsed thermography. Defect sizing is determined from the full- width- half- maximum approach. Experimental and numerical results are presented and analyzed.